2020
DOI: 10.1212/wnl.0000000000011029
|View full text |Cite
|
Sign up to set email alerts
|

Brain amyloid β, cerebral small vessel disease, and cognition

Abstract: Objective:to evaluate the association between brain amyloid-beta (Aβ) and cerebral small vessel disease (CSVD) markers, as well as their joint effect on cognition in a memory clinic study.Methods:186 memory clinic individuals, diagnosed with no cognitive impairment (NCI), cognitive impairment no dementia (CIND), Alzheimer’s dementia (AD) or Vascular dementia (VaD) were included. Brain Aβ was measured by [11C]-PiB-PET global standardized uptake value ratio (SUVR). CSVD markers including white matter hyperintens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Habes and colleagues (2018) recently showed that the increase in frontal PV-WMH precedes the accumulation of lesions at other locations, which might suggest that WMH progress from the periventricular to juxtacortical areas 50 . Given this, it is possible that the presence of WMH in the temporal lobe or juxtacortical areas, rather than being a specific pattern of distribution of WMH, might indicate that patients had a longer progression of cerebrovascular disease, probably accelerating Alzheimer’s disease (AD)-related pathology as amyloid beta accumulation (Aβ) 51 , 52 or hippocampal atrophy 53 . Similarly, age-related decline in free-recall neuropsychological tests have been shown to precede impairment in episodic memory function 54 , while the latter is relative preserved until advanced stages of cognitive impairment 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Habes and colleagues (2018) recently showed that the increase in frontal PV-WMH precedes the accumulation of lesions at other locations, which might suggest that WMH progress from the periventricular to juxtacortical areas 50 . Given this, it is possible that the presence of WMH in the temporal lobe or juxtacortical areas, rather than being a specific pattern of distribution of WMH, might indicate that patients had a longer progression of cerebrovascular disease, probably accelerating Alzheimer’s disease (AD)-related pathology as amyloid beta accumulation (Aβ) 51 , 52 or hippocampal atrophy 53 . Similarly, age-related decline in free-recall neuropsychological tests have been shown to precede impairment in episodic memory function 54 , while the latter is relative preserved until advanced stages of cognitive impairment 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the association has been found between cerebral amyloid burden and WMHs located in the posterior periventricular regions and the splenium of the corpus callosum [56]. Also, in those with cognitive impairment but not dementia, a possible synergistic effect has been observed between cerebral amyloid burden and WMH in cases of worsening cognition [57]. However, whether amyloid pathology shows a causal link with WMH progression and is associated with eventual VCI remains unclear due to lack of data, although tau protein has been implicated in the association of WMHs with impairment of cognition.…”
Section: Cerebral Aβ and Tau Burdenmentioning
confidence: 95%
“…Vascular dysfunction is integral to the AD etiology and pathophysiology, and it includes blood–brain barrier (BBB) impairment and hemodynamic dysfunction ( Klohs, 2020 ; Parodi-Rullán et al, 2020 ). CSVD also has a predictive effect on AD risk among the elderly people, and there are several epidemiological, genetic, and clinical studies related to both pathologies ( Kim et al, 2020 ; Saridin et al, 2020 ). However, whether CSVD is a cause or consequence of AD pathology still remains a controversial issue.…”
Section: Oxidative Stress and Cvsd In Admentioning
confidence: 99%